The Removal of Justice Edwards and the Struggle Between the "Legal" and the "Constitutional" in Late Nineteenth-Century New Zealand - McLay, Geoff (Victoria University of Wellington Law Review, 2022)
This article examines an extraordinary episode in New Zealand's constitutional history: the 1892 removal of Justice Worley Bassett Edwards as a Supreme Court judge after having been invalidly appointed by the previous government. Edwards' case is important as the only time a New Zealand government has formally sought to remove a sitting judge of the Supreme or (as it is now) High Court. But the article argues that the Edwards controversy is also an example of how New Zealand politicians and lawyers thought about judges within the developing New Zealand state, and even more profoundly about what was constitutional, as opposed to just legal, within that state.